How to Organize Central Securities Depositories in Developing Markets : Key Considerations - Wendt, Froukelien; Katz, Peter; Zanza, Alice (Washington, D.C. : International Monetary Fund, 2019)
The key objective of this note is to support authorities in their decision making about the optimal organization of central securities depositories (CSDs) in their country. For the purpose of this note, a CSD is defined as an entity that provides securities accounts, a securities settlement system, and central safekeeping services to market participants, which can be banks and other financial institutions. Authorities in developing markets, in particular central banks, may grapple with two questions: (1) whether to pursue a single CSD to increase market efficiencies and benefit from economies of scale and scope and (2) whether to partake in the governance of the CSD as owner or operator. This note presents seven considerations for authorities to take into account when answering these questions and determining the best model for their country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet